2011
DOI: 10.1093/ecam/neq044
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicine and Hepatocellular Carcinoma: Applications and Challenges

Abstract: Use of herbal medicine in the treatment of liver cancer has a long tradition. The compounds derived from the herb and herbal composites are of considerable interest among oncologists. In the past, certain herbal compounds and herbal composite formulas have been studied through in vitro and in vivo as an anti-hepatocellular carcinoma (HCC) agent, enhancing our knowledge about their biologic functions and targets. However there is a significant distinction between the herbal medicine and the herbal production ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 88 publications
0
37
0
3
Order By: Relevance
“…HCC is considered to be a tumour which is highly resistant to agents attacking DNA. Several herbal composite formulas and natural components (Curcumin, Resveratrol, and Silibinin) have been shown to be beneficial for the cancer chemoprevention via inducing the DNA damage [ 22 ]. In the present study, for the first time we have reported the anti-proliferative and pro-apoptotic properties of the MP in hepatic cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…HCC is considered to be a tumour which is highly resistant to agents attacking DNA. Several herbal composite formulas and natural components (Curcumin, Resveratrol, and Silibinin) have been shown to be beneficial for the cancer chemoprevention via inducing the DNA damage [ 22 ]. In the present study, for the first time we have reported the anti-proliferative and pro-apoptotic properties of the MP in hepatic cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Immunotherapy is still being explored [21]. The efficacy of tranditional Chinese medicine therapy for HCC is even less promising [22].…”
Section: Discussionmentioning
confidence: 99%
“… 11 Several herbal compounds and their composite formulas are well known and effective in both in vitro and in vivo models. 12 Despite reports on BJ as a valid cancer treatment, 13 , 14 whether or not its aqueous extract is useful against human liver cancer and the progenitor stem-like cells remained unknown. To address this topic, this study reported that low concentrations of aqueous extract of BJ not only inhibited the growth of liver cancer cells but also blocked tumor-initiating capacity of the derived spheroids.…”
Section: Introductionmentioning
confidence: 99%